PENGARUH KEPEMILIKAN PUBLIK, UKURAN DEWAN KOMISARIS, PROFITABILITAS DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Wulantika Oktariani (Jurnal Ilmiah Wahana Akuntansi, 2013)
Besides corporate financial disclosure, there is another disclosure stakeholders expect, which is corporate social responsibility disclosure. The information is needed to process short term and long term decision making. The purpose of this research is to know the influence of public ownerships, the size of the board of commissioners, profitability and firm age toward corporate social responsibility disclosure in the mining and metal companies listed in Indonesia Stock Exchange (IDX) in 2008-2011. The method used in this research is multiple linear regressions. The result showed that public ownerships has negative influence and no significant toward corporate social responsibility disclosre. Meanwhile, the size of the board of commissioners and profitability has positive and significant influence toward corporate social responsibility disclosure. And firm age has no influence toward corporate social responsibility disclosure. And public ownerships, the size of the board of commissioners, profitability and firm age simultaneously have significant effect toward corporate social responsibility disclosure. The research contributes to add social accounting litterateur and enhance awareness of improving CSR standards for mining and metal industry Keywords : Public Ownerships, The Size of The Board of Commissioners, Profitability, Firm Age and Corporate Social Responsibility Disclosure.